Pelatihan Budidaya Cabai Rawit untuk Kebutuhan Rumah Tangga di Provinsi Kalimantan Tengah: Training of Cayenne Pepper Cultivation for Household Needs in Central Kalimantan Province - Nion, Yanetri Asi; Kamillah, Kamillah; Mulyani, Rahmawati Budi; Supriati, Lilies; Djaya, Adrianson Agus; Saraswati, Dewi; Pandriyani, Pandriyani; Damanik, Zafrullah; Sinaga, Soaloon; Wardhana, Vinsen Willi; Erniaty, Erniaty (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
Cayenne pepper cultivation training to household needs is a collaboration between the Agrotechnology study program, Faculty of Agriculture, University of Palangka Raya with the Indonesian Phytopathology Association, Regional of Central Kalimantan, which has been carried out from April to December 2024 in the city of Palangka Raya and Bukit Bamba Village. The training was in counseling and also cultivation guidance through field visits for people who received chili seeds. Eighty percent of the plants distributed grew well, where 40% of the fruit could be consumed for household needs, and the cause of the failure of the chili harvest was that the plants were stolen, there were pest and disease attacks, and lack of patience or lack of interest in caring for the plants. The average successful chili harvest production per harvest per tree per week was 39 grams. This activity not only includes the distribution of cayenne pepper seeds, but also has a positive impact on the community. From the data obtained, as many as 82.14% of chili plants grew well, while 17.86% were lost, either due to theft or pest and disease attacks. The first harvest showed that 78.26% of the harvested chilies had been used for household needs, while the remaining 21.74% were still waiting for the harvest period. In terms of production, the average harvest per tree reached 39 grams, with the lowest yield of 18 grams and the highest of 66 grams. This achievement shows the great potential of cayenne pepper cultivation in increasing food security.